A Rare Cutaneous Adnexal Tumor: Malignant Proliferating Trichilemmal Tumor - Omer Alici; Musa Kemal Keles; Alper Kurt (Case Reports in Medicine)
Proliferating trichilemmal tumors (PTTs) are neoplasms derived from the outer root sheath of the hair follicle. These tumors, which commonly affect the scalp of elderly women, rarely demonstrate malignant transformation. Although invasion of the tumors into neighboring tissues and being accompanied with anaplasia and necrosis are accepted as findings of malignancy, histological features may not always be sufficient to identify these tumors. The clinical behavior of the tumor may be incompatible with its histological characteristics. Squamous-cell carcinoma should certainly be considered in differential diagnosis because of its similarity in morphological appearance with PTT. Immunostaining for CD34, P53, and Ki-67 is a useful adjuvant diagnostic method that can be used in differential diagnosis aside from morphological findings. In this study, we aimed to present the case of a 52-year-old female patient with clinicopathological features. We reported a low-grade malignant proliferating trichilemmal tumor in this patient and detected no relapse or metastasis in a 24-month period of follow-up.